Reconfiguring the place of estate-based game management: challenge, change and opportunity within rural England and Wales today - NATASHA COLEMAN (2023)
Rural land use in the UK is currently undergoing a significant transition, prompting a re-evaluation of its purpose and beneficiaries. As a key component of this transition, game management claims to occupy over two-thirds of the UK’s rural land mass and annually contributes several billion (GBP) to the economy. Despite this, the subject has remained a taboo within rural and cultural studies, with little attention paid to organised game management within private landed estates. Existing literature is often outdated, spatially biased towards Scotland's larger case examples, or overly focused on environmental or economic accounts. This empirically-driven and culturally-engaged thesis explores driven game management within English and Welsh private estates. The study aims to enhance understanding of those who manage land for this purpose and address key questions about the existence of such spatial configurations, as well as the challenges and opportunities they face. The research employs assemblage thinking as a methodological framework, using a two-fold approach referring to (1) rural stakeholder and estate-based questionnaire surveys and (2) an in-depth thematic exploration of estate case studies. The results show that despite some fluctuations, private estates and key game management actors continue to redefine value and meaning in a contemporary context. Key adaptations include strategic moves to provide and further develop estate-based activities and diversification, while retaining significant levels of game management. The research also highlights multifaceted threats and questions the succession of some forms of game management. Overall, the thesis reveals valuable insight into the private worlds of estate-based game management. The study shows how game management continues to shape rural land use, and why the subject remains contentious. By drawing attention to this aspect of our evolving countryside, the research offers a better understanding of the multifarious challenges confronting rural areas today.